Evolutions of Anisotropic Hydraulic Properties of Rough-Walled Rock Fractures under Different Shear Displacements - Dapeng Lu (Geofluids)
Four cylindrical sandstone samples were extracted from the original rectangular sample with a rough-walled fracture. Each drilling angle (θ) of cylindrical sandstone samples is different to consider the anisotropies of rough-walled rock fractures. For each sample, different flow velocities ranging from 0 m/s to 13 m/s were designed. For a given flow velocity, a series of different confining pressures (σn), including 1.5 MPa, 2.5 MPa, and 3.5 MPa, were applied on the fractured samples. The hydraulic properties of each cylindrical sandstone sample were tested under different shear displacements (us) and σn. The results show that the hydraulic gradient (J) shows an increasing trend with the increment of σn. With the increment of the Reynolds number (Re), the transmissivity (T) decreases in the form of the quadratic function. The normalized transmissivity (T/T0) decreases with the increment of J. The variations in T/T0 with J can be divided into three stages. The first stage is that T/T0 approximately holds a constant value of 1.0 when J is small indicating that the fluid flow is in the linear regime. The last two stages are that T/T0 decreases with the continuous increase of J, and the reduction rate first increases and then decreases. The critical Reynolds’ number (Rec) of the sample angle with a drilling angle of 90° is different from that of other samples. The corresponding Rec is 6.52, 28.73, and 32.1 when the shear displacement us=2 mm, 3 mm, and 4 mm, respectively. The variations in Rec and J along different drilling angles are significantly obvious. When the confining pressure is large, the effect of anisotropy on Rec is much greater than that of confining pressure.